Effect of saliva substitutes in combination with fluorides on remineralization of subsurface dentin lesions - Zandim-Barcelos, Daniela Leal [UNESP]; Tschoppe, Peter; Sampaio, Jose Eduardo C. [UNESP]; Kielbassa, Andrej M. (Springer, 2011)
Purpose Saliva substitutes are prescribed to patients suffering from radiation-induced hyposalivation to alleviate oral complaints; however, some available products have shown to demineralize dentin. The purpose of this in vitro study was to evaluate the effects of two saliva substitutes in combination or not with fluoridation on remineralization of bovine dentin subsurface lesions.Materials and methods Dentin specimens were demineralized, and stored in either mineral water (control; volvic, danone), Glandosane (cell pharm), or modified Saliva natura (SN, Medac) for 5 weeks (37 degrees C). The following treatments were applied twice daily (n=12/group): (1) no treatment; (2) immersion in pure Elmex sensitive mouthrinse (250 ppm F(-); 10 min; Gaba); (3) brushing with Duraphat toothpaste (5,000 ppm F(-); Colgate)/storage solution slurry (5 s; ratio 1: 3); (4) combination of treatments 2 and 3. Differences in mineral parameters before and after storage/treatment were microradiographically evaluated.Results After 5 weeks, Glandosane-induced a significant demineralization of dentin specimens. The mineral loss of specimens stored in Glandosane was significantly higher compared to all other solutions (p<0.05), and this side effect was inhibited by the fluoride products (p<0.05; ANOVA, Tukey). Modified Saliva natura enabled considerable remineralization, and this was significantly increased by daily application of both fluoride products (p<0.05).Conclusions Modified Saliva natura has remineralizing properties, while Glandosane is a demineralizing saliva substitute that should only be used with frequently applied fluorides in dentate patients.
Keywords: Dentin; Fluoride; Microradiography; Remineralization; Saliva Substitute